1992
DOI: 10.1002/anie.199206201
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Degradation of Cyanamide and Dicyandiamide

Abstract: Leopoldshafen 2 (FRG) on quoting the depository number CSD-56193, the names of the authors, and the journal citation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…cyanamide, according to the situation depicted in 2. Interest in this study also arose from the fact that cyanamide itself has been recognized as a substrate for both urease (yielding carbon dioxide and ammonia) [8] and Mo-nitrogenase, [9] implying its as-yet-unresolved binding to these multimetallic enzyme active sites. Unexpectedly however, several different binding modes of nitrile moieties at the bimetallic core were found in the course of these investigations, among them an intriguing coordination of cyanoguanidine (the dimeric form of cyanamide) within the clamp of the two metal ions.…”
Section: Introductionmentioning
confidence: 98%
“…cyanamide, according to the situation depicted in 2. Interest in this study also arose from the fact that cyanamide itself has been recognized as a substrate for both urease (yielding carbon dioxide and ammonia) [8] and Mo-nitrogenase, [9] implying its as-yet-unresolved binding to these multimetallic enzyme active sites. Unexpectedly however, several different binding modes of nitrile moieties at the bimetallic core were found in the course of these investigations, among them an intriguing coordination of cyanoguanidine (the dimeric form of cyanamide) within the clamp of the two metal ions.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have revealed that the inhibitory potential of dicyandiamide (DCD) can curb nitrate leaching by up to 76% (Di and Cameron, 2004) and N 2 O emissions by up to 70% (Di et al, 2007). Yet for all its effectiveness, degradation in soil limits the persistence of DCD (Estermaier et al, 1992), which has a half-life estimated between 110 d at 5°C and approximately 20 d at 25°C (Kelliher et al, 2008). Consequently, repeated soil applications are required to maintain efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…2003). This finding is surprising because cyanamide has long been believed to be absent in nature (Estermaier et al . 1992; Maier‐Greiner et al .…”
Section: Introductionmentioning
confidence: 97%